2011
DOI: 10.1007/s12206-011-0741-0
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy simulation and acoustic analysis of a turbulent flow field in a swirl-stabilized combustor

Abstract: To conduct a comprehensive study on the flow characteristics and acoustic oscillation in a gas turbine combustor, a 3D large-eddy simulation (LES) was implemented. The formulation consists of the Favre-filtered conservation equations of mass, momentum, and energy. The subgrid-scale dynamics are modeled using a compressible flow version of the Smagorinsky model. To investigate the dominant coherent structure, the proper orthogonal decomposition (POD) method was used for post-processing. The combustor of concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The coefficient, CI, can be calculated in a leastsquare method to minimize the error: preconditioning scheme [11]. The code is paralleled using an MPI library for more effective calculation [12][13][14].…”
Section: Filtered Governing Equationsmentioning
confidence: 99%
“…The coefficient, CI, can be calculated in a leastsquare method to minimize the error: preconditioning scheme [11]. The code is paralleled using an MPI library for more effective calculation [12][13][14].…”
Section: Filtered Governing Equationsmentioning
confidence: 99%
“…The real-gas fluid thermodynamic relation is applied to a preconditioning scheme [20]. The code is paralleled using an MPI library for a more effective calculation [21][22][23]. Figure 1 shows the coaxial swirl injector geometry as well as the swirl numbers of liquid oxygen, and kerosene, at 1.598 and 6.548, respectively [24].…”
Section: Numerical Schemementioning
confidence: 99%
“…11 shows the timeaveraged mixing efficiency. In both models, the efficiency increases as it moves downstream after the (21) where Y Fuel is the mass fraction of kerosene. The parameter α is determined by relating the local equivalence ratio, ϕ local to the global equivalence ratio, ϕ glocal .…”
Section: Effects Of Dynamic Sgs Modelmentioning
confidence: 99%
“…LES methods are very effective for studying various turbulence characteristics of swirl stabilized combustor. They can be effectively used for treatment and studying dissipation of vortex breakdown and swirl structure, as well as angular recirculating zone and central recirculating zone, important characteristics of swirl (Kim et al 2011, Tiwari et al 2020. Canepa et al (2006) has shown that the complex flow field structure comes from vortex breakdown.…”
Section: Introductionmentioning
confidence: 99%